The influence of parents and peers on adolescents' problematic social media use revealed. (June 2023) - Leijse, Merel M.L.; Koning, Ina M.; van den Eijnden, Regina J.J.M.
Abstract: Nowadays, parents, caretakers, teachers and researchers have an increasing interest in the development and consequences of problematic social media use, especially among adolescents. A growing body of research investigates factors that may influence the development of problematic social media use. This study examined the role of the broader context of parental (time spent with parents and family support), peer (peer support and peer pressure), and individual factors (perceived self-control) in the development of adolescents' risky and problematic social media use (ref = normative), as well as the moderating role of self-control by using a longitudinal design. Adolescents ( N  = 1384) aged 11–19 years ( M age  = 14.1, SD  = 1.03) were included and completed a self-report questionnaire twice (6-month interval). A Multinomial Logistic Regression showed that parent and peer factors predicted risky social media use, but not problematic use of social media. Adolescents' level of self-control did not modify these relationships. However, low self-control did increase the odds of developing risky or problematic social media use directly. In conclusion, this study provides preliminary evidence that general parent and peer factors can help to prevent risky social media use, but to a lesser extent problematic use of social media. For the latter, the individual factor self-control, however, seems to play a role. Highlights: For some adolescents, the use of social media can be risky or problematic. Parents and peers have a protective role in adolescents' risky social media use. Parent and peer factors did not predict adolescents' problematic social media use. Self-control is not a significant moderator. Low self-control is a predictor of risky and problematic social media use.